Peran Pendidikan dalam Memoderasi Pengaruh Literasi Keuangan, Inklusi Keuangan dan Digitalisasi Keuangan terhadap Keberlanjutan Usaha Mikro Kecil dan Menengah (UMKM) di Jakarta Pusat - Siti Mariyam; Heri Ispriyahadi (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the effects of financial literacy, financial inclusion, and financial digitalization on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Central Jakarta and to examine the role of education as a moderating variable, motivated by the low capability of MSME owners in managing finances and utilizing formal financial services. This research employs a quantitative approach using a survey method by distributing questionnaires to 210 MSME owners operating in Central Jakarta, with data analyzed using Structural Equation Modeling (SEM). The results indicate that financial literacy, financial inclusion, and financial digitalization have positive and significant effects on MSME sustainability, suggesting that improved financial understanding, access to formal financial services, and the utilization of digital financial technology enhance business stability and resilience. Education does not strengthen the relationship between financial literacy and MSME sustainability; however, it significantly strengthens the effect of financial inclusion on MSME sustainability and significantly moderates the relationship between financial digitalization and MSME sustainability with a negative direction. This study is limited to MSMEs located in Central Jakarta and relies on perception-based data, which restricts the generalizability of the findings, yet it provides empirical contributions to the development of MSME empowerment policies and strategies focusing on financial literacy, financial inclusion, and financial digitalization.